Uomini e "cocci": i contesti ceramologici del Quartiere Bizantino del Pythion in una prospettiva antropologica (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The excavation in the so called Byzantine District near the Pythion shrine at Gortyn (Crete) brought to light a number of ceramic assemblages that deserve to be investigated not only to get a date or to study the economic processes of production and distribution of pottery. They can be investigated under an anthropological perspective too, as indicators of complex human behavior in that particular context of space/time. From this point of view, the potsherds can provide relevant informations about the ways of urban life in the district, the disposal of solid urban refuses and the natural catastrophes as element of transformation of urban fabric in Late Antique and Early Byzantine age.
Keywords: Gortyn; Crete; Pottery; Late Antiquity; Early Byzantium; Anthropology; Refuses; Daily life